Answer:
x=3 y=4
Explanation:
Y=(-x)+7
Y=x+1
You take the first equation, (-x)+7, and substitute it for the second Y. It will look like this (-x)+7=x+1
Now you have to add x to both sides because you have to do the opposite of (-x). When you add x to both sides, you are left with, 7=2x+1. Then you have to subtract 1 from both sides because the opposite of +1 is (-1). You are left with 6=2x. Then you have to divide both sides by 2 to get the variable by itself. You are left with x=3. That is your x-value. Then you plug in x in any equation. I chose the bottom one. y=x+1 is changed to y=3+1. Y=4.
(3,4)